Travel on a song-the roots of Zanzibar taarab - Kiel, Hilda (International Library of African Music, 2012)
Zanzibar, in the Indian Ocean off the coast of Tanzania, consists of the neighbouring islands Unguja and Pemba which are home to a music style called taarab — a distinct musical form that blends Arabic and African as well as Indian, Latin, Indonesian and European influences. This style of music can be found with variations all along the Swahili Coast in Tanzania and Kenya, with the degree of influence from different musical cultures varying from place to place. Egyptian Arabic influence is most audible in Zanzibar taarab, while Mombasa (Kenya) exhibits a more pronounced Indian influence and Lamu (Kenya), has remained closer to its Yemeni origins.
Keywords: African Music